Unemployment Compensation Finance and Labor Market Rigidity - Pierre Cahuc; Franck Malherbet (Institute for the Study of Labor (IZA), 2002)
The systematic use of experience rating is an original feature of the U.S. unemployment benefit system. In most states, unemployment benefits are financed by taxing firms in proportion to their separations. Experience rating is a way to require employers to contribute to the payment of unemployment benefits they create through their firing decisions. It is striking that experience rating is absent from the unemployment compensation systems of other OECD countries, where benefits are usually financed by taxes on payrolls, paid by employers or employees, and by government contributions (Holmlund, 1998). Is experience rating only adapted to the U.S. labor market? Would it be suitable in other countries? At first glance, it is likely that experience rating is not desirable in many European labor markets characterized by high firing costs. We provide a simple matching model of a rigid labor market including firing costs, temporary jobs and a minimum wage in order to analyze the issue. Our analysis leads us to argue that experience rating is likely to reduce unemployment and to improve the welfare of low skilled workers in France, and more generally for low skilled workers in a typical rigid Continental European labor market.
Keywords: J65; J41; J64; 330; unemployment benefits; job protection; matching models; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Humankapital; Arbeitsplatzsicherung; Arbeitslosenversicherung; Vereinigte Staaten